MINING AND METALLURGICAL COMPLEX IN INDUSTRIAL AND POSTINDUSTRIAL DEVELOPMENT OF SOCIETY - Rakishev Bayan (Academic Journal of Physical and Chemical Sciences, 2019)
Development of the human society is directly related to the use of natural materials. Depending on the processing degree of the used material from mineral raw materials as the tools of labor, theStone, Bronze andIron Ages are distinguished. Subsequently, in the period of industrial development of society, articles made of highquality metals and alloys were used as means of production, and in the period of post-industrial development, items made of high-tech metals and alloys were used. By the name of these materials, new stages in the development of civilization are called the “age” of high-quality metals and alloys and the “age” of high-tech metals and alloys, respectively. The main characteristics of the stages of the human society development are given.